Salivary concentrations of Streptococcus mutans and Lactobacilli during an orthodontic treatment. An observational study comparing fixed and removable orthodontic appliances - Stefano Mummolo; Marco Tieri; Alessandro Nota; Silvia Caruso; Atanaz Darvizeh; Francesca Albani; Roberto Gatto; Giuseppe Marzo; Enrico Marchetti; Vincenzo Quinzi; Simona Tecco (Wiley, 2020)
Abstract Aim This study aimed to investigate salivary concentrations of Streptococcus mutans (S. mutans) and some Lactobacilli, and plaque index (PI) in patients wearing fixed versus removable orthodontic appliances. Methods A sample of 90 orthodontic patients (56 males and 34 females) was included in the study: 30 subjects (aged 21.5±1.5 years) were treated with removable clear aligners (CA), while for other 30 cases (aged 23.3±1.6 years) a fixed multibrackets appliance (MB) were utilized, and 30 patients (aged 18.2 ±1.5 years) wearied a removable positioner (RP). Salivary concentrations of S. mutans and Lactobacilli and PI were evaluated prior to start of the orthodontic treatment, after 3 months and 6 months. Results After 6 months, 40% of MB patients (12 subjects over 30) showed a concentration of S. mutans associated to high risk of developing tooth decay (CFU/ml>105), differently from participants wearing removable appliances (odds ratio = 5.05; 95% C.I. = 1.72‐14.78; chi‐square = 9.64; p = 0.0019). The same trens was observed for the concentration of Lactobacilli (odds ratio = 4.33; 95% C.I. = 1.53‐12.3; chi‐square = 8.229; p = 0.004). In addition, over the duration of the study, CA patients maintained PI at 0 level, while MB patients experienced a statistically significant increasing trend of PI over time, and their PI became clinically/statistically relevant after 6 months, respect to CA and RP patients. Conclusions Comparing all the data, while, after 6 months, only about 10% of CA patients and 13.3% of RP patients achieved a microbial colonization which may lead to high risk of caries development, about 40% of MB patients ‐ and 20% after 3 months ‐ showed a high level of vulnerability to developing caries, which require additional strategies for plaque control and microbial colonization to be employed.